Evaluation of Vascular Endothelial Growth Factor, Irisin, Copeptin Levels and Some Biochemical Factors in Patients With Polycystic Ovary Syndrome in Samarra City - Qaisar Mashan Abd (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study was conducted in the laboratories of Samarra Teaching Hospital and some private laboratories in the city of Samarra in salah aldiyn Governorate for a period from 1/8/2024 to 1/9/2024, where the study included (50) samples of women of reproductive age, ranging in age from (20-40) years, and were distributed into two groups: Patient group: (30) samples were from female patients with PCOS, Control group: (20) samples of healthy women. The pathological cases of women suffering from PCOS were confirmed after conducting clinical examinations and referring them to the specialist doctor and performing an ultrasound examination. after that, blood was taken from both groups (patients and healthy women) and separated using a centrifuge. Then the sex hormones Luting hormone -LH, Folic stimulating hormone-FSH, and some biochemical variables, which included (Vascular endothelial growth factor-VEGF , Irisin, Copeptin). The results of the this study showed a significant rise in each of the hormones (LH. FSH, Testosterone ,Copeptin, VEGF) and a significant low in (Irisin) in the blood serum of women infected with PCOS compered a healthy women , with a probability of P ≤ 0.05.